دراسة مدى تحقق العدالة الضريبية في الواقع - الضريبة على الدخل أنموذجا- - نبق, بوبكر; مخلوفي, الطاهر; بدراوي, يحي (جامعة الوادي - University of Eloued, 2021)
الضريبة كوسيلة اساسية من الوسائل المالية التي تساهم في تمول خزينة الدولة وتحقيق التنمية الاقتصادية، والادارة الضريبية تسعى جاهزة لتحقيق العدالة بين المكلفين من جهة والحد من التهرب الضريبي، ولهذا كان هذا البحث لتسليط الضوء على مدى تحقيق العدالة الضريبية بأخذ نماذج من الضرائب على الدخل واجراء مقارنة بينها مثل مداخيل الاجراء في القطاعين العام والخاص من جهة، وبعض المكلفين من غير الاجراء. ولقد خلصت الدراسة انه لا توجد عدالة ضريبية بالمفهوم الذي يهدف اليه المشرع الجزائري إذا اعتبرنا ان المكلفين يختلفون في تحملهم تحديد الوعاء الضريبي والتصريح بالمداخيل وكذا تحملهم التصريح الضريبي اتجاه الادرة المعنية. فكانت النتيجة ان الاجراء لديهم مساهمة أكبر في تمويل خزينة الدولة من الضريبية بمقارنتهم مع غير هم. The tax is considered an essential resource in financing the state treasury, and a financial tool that contributes to achieving economic development. In light of this pivotal role, tax administration is striving seriously to achieve justice among taxpayers on one hand, and to limit tax evasion on the other hand. Hence, our research came to shed light on the extent to which tax justice is actually achieved, through taking a sample of income taxes and making a comparison between them, such as tax on wages in public and private sectors, and other income taxes. The study concluded that there is no tax justice in the sense that the Algerian legislator aims for, especially if we consider that the taxpayers differ in the extent to which they bear the determination of the base and the tax declaration towards the concerned administration. In addition, the contribution of employees was greater in financing the state treasury than other taxpayers
Study of the Extent to Which Tax Justice is Achieved in Reality –The Income Tax Case
مقال
Keywords: الضريبة. ; التهرب الضريبي. ; الوعاء الضريبي ; العدالة الضريبية